Sun Protection Behaviors Associated with Self-Efficacy, Susceptibility, and Awareness among Uninsured Primary Care Patients Utilizing a Free Clinic - Akiko Kamimura; Maziar M. Nourian; Jeanie Ashby; Ha Ngoc Trinh; Jennifer Tabler; Nushean Assasnik; Bethany K. H. Lewis (Dermatology Research and Practice)
Background. Skin cancer is the most commonly diagnosed form of cancer in the United States (US). However, knowledge, behaviors, and attitudes regarding sun protection vary among the general population. The purpose of this study is to examine sun protection behaviors of low-income primary care patients and assess the association between these health behaviors and the self-efficacy, susceptibility, and skin cancer awareness. Methods. Uninsured primary care patients utilizing a free clinic (N=551) completed a self-administered survey in May and June 2015. Results. Using sunscreen was the least common tactic among the participants of this study. Skin cancer awareness and self-efficacy are important to improve sun protection behaviors. Spanish speakers may have lower levels of skin care awareness compared to US born and non-US born English speakers. Male and female participants use different sun protection methods. Conclusion. It is important to increase skin cancer awareness with self-efficacy interventions as well as education on low-cost sun protection methods. Spanish speaking patients would be a target population for promoting awareness. Male and female patients would need separate gender-specific sun protection education. Future studies should implement educational programs and assess the effectiveness of the programs to further promote skin cancer prevention among underserved populations.